Don't expect left ventricular reverse remodeling after cardiac resynchronization therapy in patients with systolic heart failure and atrioventricular block: A multicenter study. (15th October 2016) - Sairaku, Akinori; Yoshida, Yukihiko; Nakano, Yukiko; Hirayama, Haruo; Maeda, Mayuho; Hashimoto, Haruki; Kihara, Yasuki
Abstract: Background: The BLOCK HF trial showed that heart failure patients with atrioventricular block (AVB) and left ventricular systolic dysfunction (LVSD) are considered good candidates for cardiac resynchronization therapy (CRT), even though they have a narrow QRS duration. We aimed to compare the clinical response to CRT between patients with AVB combined with LVSD and patients with pre-existing CRT indications. Methods: We compared the clinical data on CRT across the following 3 groups in 3 cardiovascular centers; heart failure patients with an LV ejection fraction (LVEF) of ≤ 35% who had a QRS duration of ≥ 120 ms (standard indication, n = 125), those needing an upgrade to CRT (upgrade, n = 49), and patients with an LVEF of ≤ 50% who had advanced AVB (AVB with LVSD, n = 27). Results: The prevalence of left bundle branch block differed significantly across the groups (87.2%, 98.0% and 40.7%; P < 0.001). No inter-group difference was found in the percentage of patients in whom clinical composite score (CCS) assessed 6 months after the CRT was improved (60.8%, 57.1% and 70.4%; P = 0.67). Whereas, even among the patients with an improved CCS, a significantly smaller LV end-systolic volume reduction after the CRT was seen in the ABV with LVSD group (− 35.3 ± 34.7, − 21.4 ± 28.5 and − 5.2 ± 23.9%; P = 0.001). The incidence of cardiovascular death or hospitalization from heart failure within 5 years occurred with a similar frequency (44%, 55.1% and 44.4%; P = 0.9). Conclusions: As compared to patients with preexisting CRT indications, CRT may be similarly effective for patients with AVB and LVSD, however, LV reverse remodeling may be uncommon among them.